Dinamika Tantangan Pembelajaran Pendidikan Agama Islam di Era Digital - Syifa Adilla Zahra; Syifaul Karima, Nur Rohfitta; Wildayah Musyafa; Zulhannan; Untung Sunaryo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the challenges in the learning process of Islamic Religious Education (PAI) in the digital era, particularly those related to improving teachers' competencies, the relevance of learning materials, and students’ preparedness in facing technological advancements. The method used is a literature review with content analysis and a hermeneutic approach to interpret the meaning of various source materials. The findings indicate that the use of digital technology has transformed the way PAI is taught, shifting from traditional methods to the use of digital tools. However, obstacles remain, such as low digital literacy, limited access to technology, and the risks of internet misuse. Therefore, efforts are needed to enhance teachers' capabilities, develop contextually appropriate digital learning materials, and strengthen students’ digital literacy so that PAI can continue to effectively shape the character and spiritual values of the younger generation.